Analisis Masalah dan Solusi Prioritas Pengembangan UMKM - Septiana, Nurul Izzati; Rozi, A. Fahrur; Muar, Romli (Universitas Islam Raden Rahmat, 2019)
This research is a qualitative-quantitative analysis that aims to capture a value or view represented by experts and practitioners about problems, solutions, and strategies for developing SMEs in Palaan village. The analytical tool used is the ANP method and is processed using the